2008
DOI: 10.1158/0008-5472.can-08-0601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Properties of Water-Soluble Zinc Ionophores

Abstract: Several water-solubilized versions of the zinc ionophore 1-hydroxypyridine-2-thione (ZnHPT), synthesized as part of the present study, have been found both to increase the intracellular concentrations of free zinc and to produce an antiproliferative activity in exponential phase A549 human lung cancer cultures. Gene expression profiles of A549 cultures treated with one of these water-soluble zinc ionophores, PCI-5002, reveal the activation of stress response pathways under the control of metal-responsive trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 20 publications
4
77
0
2
Order By: Relevance
“…In support of this, zinc administration has been shown to enhance the therapeutic indices of various antineoplastic agents (34,35). Interestingly, zinc by itself has been shown in xenograft models to be an effective antitumoral agent (36,37), as well as being implicated in the mechanism of action of novel therapies (38)(39)(40)(41). There are multiple studies suggesting that zinc addition to chemotherapeutic agents improves their antitumoral capacity, in xenograft models (20,42) as wells as in humans (43,44), and against chemoresistant cells (45).…”
Section: Discussionmentioning
confidence: 94%
“…In support of this, zinc administration has been shown to enhance the therapeutic indices of various antineoplastic agents (34,35). Interestingly, zinc by itself has been shown in xenograft models to be an effective antitumoral agent (36,37), as well as being implicated in the mechanism of action of novel therapies (38)(39)(40)(41). There are multiple studies suggesting that zinc addition to chemotherapeutic agents improves their antitumoral capacity, in xenograft models (20,42) as wells as in humans (43,44), and against chemoresistant cells (45).…”
Section: Discussionmentioning
confidence: 94%
“…When added to cells along with zinc it induced apoptosis (37)(38)(39). Although the sodium salt of pyrithione is water soluble, the zinc salt is not, prompting the synthesis and description of several water soluble derivatives designed to be used as anticancer drugs (23).…”
Section: Recognition That Some Metal-binding Compounds Act As Ionophomentioning
confidence: 99%
“…We have reported that clioquinol targets both Akt and MAP kinase pathways when inducing apoptosis of cancer cells (17,25). Magda described water soluble zinc ionophores that activate stress response pathways involving the metal-responsive transcription factor 1, the hypoxia-inducible transcription factor 1, and heat shock transcription factors (23). It is likely that additional mechanisms will be discovered, and the ability of a given drug to affect multiple pathways may determine its ultimate clinical usefulness.…”
Section: Other Mechanisms Of Actionmentioning
confidence: 99%
“…16 More recent studies have shown that this property can be used to kill cancer cells selectively. 17 The studies in the current report describe our attempt to characterize possible mechanisms behind this cell death process using Saccharomyces cerevisiae. Paradoxically, it was possible to increase either the sensitivity or the resistance of yeast to zinc by knocking out alternative sets of autophagy genes.…”
Section: Znmentioning
confidence: 99%